Heavy metal levels and sources in suspended particulate matters of the glacier watersheds in Northeast Tibetan Plateau - Wu, Rui; Dong, Zhiwen; Cheng, Xiping; Brahney, Janice; Jiao, Xiaoyu; Wu, Lihua (Frontiers in Environmental Science, 2022)
This study collected summer meltwater runoff samples from several glacier watersheds of the northeast Tibetan Plateau during June-July 2017, and measured the concentrations of 17 trace elements (Li, Be, Sc, V, Cr, Co, Ni, Cu, Zn, Ga, Rb, Mo, Cd, In, Sb, Cs, Ba) in meltwater suspended particulate matter (SPM), in order to reveal the elemental concentration, spatial distribution, and water quality in remote glacier watershed under regional anthropogenic activities. Results showed that, the concentration of heavy metal elements was relatively high in Yuzhufeng Glacier basin, ranging from 0.57 μg/L (In) to 1,551.6 μg/L (Ba), whereas in Qiyi Glacier basin it was the lowest, ranging from 0.02 to 85.05 μg/L; and relatively medium in other glacier watersheds, with total elemental concentration varying from 1,503.9 to 1726.2 μg/L. Moreover, enrichment factors (EFs) of SPM heavy metals showed significantly higher value in the downstream than that of upper glacier region of the watershed. Most heavy metals with low EFs mainly originated from crust dust, while others with higher EFs (e.g., Cd, Sb) probably originated from anthropogenic sources. Spatially, the EFs of heavy metals were higher in Yuzhufeng and Laohugou Glacier basins; while in other regions the EFs were relatively low, which may be caused by regional land-surface and atmospheric environmental differences surrounding the various glacier watersheds. Compared with other remote locations in global range, heavy metals level (e.g., Cu, Ni, and Zn) in this region is relatively higher. Meanwhile, we find that, though the water quality of the glacier basin in northeast Tibetan Plateau was relatively clean and pollution-free, it is still obviously affected by regional anthropogenic activities. Mining activities, transportation and natural weathering and erosion processes in the study areas have important effects on the content of heavy metal pollutants of river-water SPM in the glacier watershed. Moreover, backward air-mass trajectories demonstrated the potential atmospheric pollutants transport from the surrounding cities and suburbs, to deposit in the snowpack and glaciers, and then melted out and released into meltwater runoff. This study provides a new perspective on more complete view of heavy metals distribution in glacier watershed, and new understanding for the cryosphere water environment evaluation in the Tibetan Plateau region.